THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF COST MANAGEMENT FOR THE PRODUCTION OF BUILDING MATERIALS - Molodets, Andrii (Social Development: Economic and Legal Issues, 2025)
Cost control is of particular importance in modern market conditions, as the effective regulation of expenditure activities directly impacts product cost, the enterprise’s financial results, and its capacity for innovative development. Currently, Ukraine virtually lacks a holistic and systematic cost control model that defines corporate policy for rationalizing resource-intensive activities. The research aim is to study the theoretical and methodological foundations of cost management for the production of building materials. The scientific article defines the key organizational conditions for the production of building materials. It outlines the main elements of the production cost control system, which include: cost regulation, strategic cost forecasting, integrated resource planning (ERP), adaptive resource normalization, operational economic analysis, process-oriented costing, deviation control and real-time response, cost optimization, cost auditing, feedback, and corrective management. The analytical elements of the cost management system during the production of building materials are presented as follows: cost forecasting and planning; cost normalization; cost calculation; cost accounting; cost and cost price analysis; and control and regulation of the cost management process. Cost accounting is carried out in accordance with a defined nomenclature of cost items, within which the accumulation and allocation of costs by costing objects are reflected. Particular attention is paid to the precise determination of the actual cost price of products based on classification approaches (by economic content, cost items, place of occurrence, etc.), which is critically important for construction-profile enterprises. The methodological essence of the cost management system lies in forming a comprehensive mechanism for integrating the processes of supply, consumption, control, and regulation of resource flows in accordance with established strategic and tactical objectives. The key characteristics of such a system are purposefulness, flexibility, adaptability, manageability, and the ability to transform under the influence of external and internal factors.